Absorption, Distribution and Excretion of Radioactivity by Male Rats after a Single Intravenous or Subcutaneous Dose of 14C-azacitidine - Ichikawa, T.; Suda, Y.; Nakagawa, T.; Nonaka, K.; Nakamura, A.; Ochi, S. (Drug Research, 2013)
The absorption, distribution and excretion of radioactivity were investigated in male Sprague-Dawley rats after a single intravenous or subcutaneous dose of 14C-azacitidine. After subcutaneous administration, 14C-azacitidine was rapidly absorbed and the radioactivity was distributed to the tissues. The absorption of radioactivity after subcutaneous administration was 76.6% of that observed after intravenous administration. There were no marked differences in the tissue distribution of the radioactivity between administration routes. The concentrations of radioactivity in most tissues, including the spleen and bone marrow, which are sites of action of azacitidine, were higher than those in the plasma. Particularly high concentrations of radioactivity were detected in the spleen, kidney and liver. The accumulation of radioactivity in blood cells increased from 0.5 to 48 h. The binding of azacitidine to serum protein was low at <9%, and the cumulative urinary and fecal excretion of radioactivity for 168 h after intravenous or subcutaneous administration was >95% of the administered dose, indicating that radioactivity did not accumulate in the tissues. The radioactivity was mainly excreted in the urine.
Keywords: CAS 320-67-2; azacitidine; absorption; distribution; excretion; pharmacokinetics